Every little letter - Underwood, Deborah (Dial Books for Young Readers, 2020)
In a world where all the letters of the alphabet live in separate cities surrounded by walls, little h and small i's newfound friendship inspires all the divided communities to connect and form such words as courage, cooperate, and kindness. How do you tear down walls? With words at first, then brick by brick